2007
DOI: 10.1021/jp065173a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Self-Assembly at Bare Semiconductor Surfaces:  Investigation of the Chemical and Electronic Properties of the Alkanethiolate−GaAs(001) Interface

Abstract: High-resolution X-ray photoelectron spectroscopy (HRXPS), time-of-flight secondary ion mass spectrometry (ToF-SIMS), and Raman scattering have been used to characterize the bonding and electronic properties of the interfaces formed by ambient-temperature, solution self-assembly of octadecanethiol and dodecanethiol under oxygen-free conditions on GaAs(001) surfaces. The combination of HRXPS and ToF-SIMS shows that both monolayers form direct S−[GaAs] attachment to the bare substrate with dominant As−S bonding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
169
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(196 citation statements)
references
References 96 publications
27
169
0
Order By: Relevance
“…Long-chain alkanethiol selfassembled monolayers ͑SAMs͒ on GaAs͑001͒ have been studied in this context by a number of authors, both from the perspective of fundamental material science [1][2][3][4][5][6][7][8][9][10] and as a potential route to applications including surface passivation, 11 metal-molecule-semiconductor junctions, 12,13 the assembly of DNA hybridization probes, 14 and the immobilization of functional proteins such as avidin. 15 In these studies, Fourier transform infrared ͑FTIR͒ spectroscopy is frequently employed to investigate important SAM structural parameters such as molecular orientation 16 and the fraction of conformational defects.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain alkanethiol selfassembled monolayers ͑SAMs͒ on GaAs͑001͒ have been studied in this context by a number of authors, both from the perspective of fundamental material science [1][2][3][4][5][6][7][8][9][10] and as a potential route to applications including surface passivation, 11 metal-molecule-semiconductor junctions, 12,13 the assembly of DNA hybridization probes, 14 and the immobilization of functional proteins such as avidin. 15 In these studies, Fourier transform infrared ͑FTIR͒ spectroscopy is frequently employed to investigate important SAM structural parameters such as molecular orientation 16 and the fraction of conformational defects.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur is chemically more reactive than oxygen so that replaces oxygen to form electrically stable surface sulfides. These reactions may be called interfacial self-cleaning reactions which are confirmed by XPS measurements [11,16]. The sulphur interaction with the InAs creates In x S y and As x S y (InAs + 2HS = In x' S y' +As x" S y" +H 2 ) and interaction with the GaSb creates Ga x S y and Sb x S y (GaSb + 2HS = Ga x' S y' + Sb x" S y" +H 2 ) on the surface.…”
Section: Resultsmentioning
confidence: 87%
“…It cleans the surface from conductive native oxides and satisfies dangling bonds [10][11][12]. Although thiol is mostly studied on GaAs [13][14][15][16] surfaces, some studies on InP [17], GaP [18], and InAs [11,12] and other III-V compounds have also been reported. McGuiness et al has shown that long chained octadecanethiol strongly reduces As and Ga oxides and prevents subsequent surface oxide re-growth [16] using X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3,14] Recently, there has been an interest in extending such studies to III-V semiconductor substrates. [10,12] Gallium phosphide (GaP) is an attractive semiconductor material due to its usage in charge storage devices [23] and low-noise detection photodiodes. [19,24,25] This material offers promise for the fabrication of novel biosensors.…”
mentioning
confidence: 99%